2008
DOI: 10.3892/or.19.4.881
|View full text |Cite
|
Sign up to set email alerts
|

Expression of rTSβ as a 5-fluorouracil resistance marker in patients with primary breast cancer

Abstract: Abstract. Expression of thymidylate synthase (TS) in tumor cells is frequently suggested as an important prognostic factor for patients scheduled for chemotherapy with 5-fluorouracil (5-FU). However, clinical evidence does not fully support such an anticipation. We studied the expression of rTSß, a reverse orientation gene of TS, as a 5-FU resistance marker in patients with primary breast cancer. Expression of rTSß was examined in 129 patients with newly diagnosed breast cancer and five breast cancer cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In clinical studies, rTSβ was found to be expressed in breast cancer tissue but not the surrounding tissues. 8 Furthermore, a statistically significant correlation was found between the level of rTSβ expression and a decrease in the five year survival rate of colon cancer patients. 5 The 27 residue longer N-terminus of rTSγ, compared to rTSβ, is proposed to constitute a mitochondrial signaling sequence, 9 suggesting that rTSβ and rTSγ serve similar enzymatic functions.…”
Section: Introductionmentioning
confidence: 89%
“…In clinical studies, rTSβ was found to be expressed in breast cancer tissue but not the surrounding tissues. 8 Furthermore, a statistically significant correlation was found between the level of rTSβ expression and a decrease in the five year survival rate of colon cancer patients. 5 The 27 residue longer N-terminus of rTSγ, compared to rTSβ, is proposed to constitute a mitochondrial signaling sequence, 9 suggesting that rTSβ and rTSγ serve similar enzymatic functions.…”
Section: Introductionmentioning
confidence: 89%
“…The same group also reported a statistically significant decrease in five year survival of colon cancer patients with tumor hsENOSF1β expression compared to colon cancer patients without tumor hsENOSF1β expression [ 29 ]. Taken together, in vitro cell culture data [ 23 - 27 ] and human patient data [ 28 , 29 ] suggest a connection between hsENOSF1β expression and cancer.…”
Section: Introductionmentioning
confidence: 95%
“…In cell culture, hsENOSF1β expression appears to be regulated by environmental factors such as cell density, time in culture, and exposure to chemotherapy drugs that affect thymidylate synthase or folate pathway enzymes [ 23 - 27 ]. Using patient samples from a Taiwanese population, Kuo et al [ 28 ] showed that hsENOSF1β is expressed in breast tumor tissue and not surrounding tissue. The α or γ splice forms were not found in the patient samples [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5‐FU undergoes complex anabolic and catabolic biotransformation. Gene products involved in this transformation include dihydropyrimidine dehydrogenase (DPD or DPYD ), which breaks down 5‐FU,84–88 and those drug targets (eg, thymidylate synthase [TS or TYMS ])89, 90 and methylenetetrahydrofolate reductase ( MTHFR ). Several of these genes have been shown to affect 5‐FU treatment outcomes.…”
Section: Examplesmentioning
confidence: 99%